PREVALENCE AND RISK FACTORS OF ACTIVE TUBERCULOSIS AMONG HIV- POSITIVE CLIENTS RECEIVING ANTIRETRO VIRAL THERAPY AT VILLA MARIA HOSPITAL, KALUNGU DISTRICT: A CROSS SECTIONAL DESCRIPTIVE STUDY. - SSENTEZA MATHIUS; Jonathan Kazibwe; Godfrey Mugisa (Student's Journal of Health Research, 2023)
Background With the introduction of antiretroviral therapy (ART), TB remains a leading Co-infection among people living with HIV while on ART, responsible for 30% of deaths among PLHIV in Uganda. This study was designed to determine the prevalence and risk factors leading to the development of active tuberculosis among HIV-positive clients receiving ART from Villa Maria Hospital in Kalungu district. Methodology A cross-sectional descriptive study that employed qualitative data collection methods was conducted among 160 HIV-positive clients. Participants with TB symptoms were diagnosed with TB using smear microscopy (Zn), gene-expert, and urine TB lam and chest x-ray. Data was collected, and analyzed by Microsoft Excel 2013, and results were presented in tables & figures. Results Among the participants, 44.4% and 55.6% were male & female respectively with a median age of 45 years. 25 (15.6%) of the patients had developed active TB infection, which was independently associated majorly with advanced HIV disease & non-users of TPT. The use of IPT & good adherence to ART reduced the risk of developing TB by over 80%. 33.8% didn't know how TB spreads, and coughing, and living with a TB patient were the most identified ways in which TB spreads, Lack of food & long distances to the health centers were the major hindrances to completing TB treatment. Pill burden & frequent movement to health centers were the major challenges faced during TB treatment. Conclusions HIV clients with cough, advanced HIV disease, and non-users of TPT had an increased risk of developing TB infection. However, the use of TPT and good adherence to ART reduced the risk of TB among HIV-infected patients. Therefore, early screening of TB among HIV patients with cough, and involvement of VHTs/CHWs and community-based organizations (CBOs) to increase the awareness and control measures of TB in the communities.